Transformations of Romanness Early Medieval Regions and Identities - Pohl, Walter; Gantner, Clemens; Grifoni, Cinzia; Pollheimer-Mohaupt, Marianne (Millennium-Studien / Millennium Studies, 2018)
Few pre-modern empires had an impact on their subjects comparable to that of the Roman Empire. Over time, being Roman could mean many different things, e.g. Latin speakers under barbarian rule, subjects of the Byzantine empire or Christians in post-Roman Syria. This volume explores the changes Roman identity underwent in most of the former provinces of the empire between c. 400 and c. 1000, offering the first comprehensive overview on this topic.